Comparative Analysis of Electronic Structures Calculations: A Simple Test Case Set for Kohn-Sham Density Functional Theory and Hartree-Fock Methods - Apriliyanto, Yusuf Bramastya; Nurrosyid, Naufan (Indonesian Journal of Chemical Studies, 2023)
A comparative analysis on the performance of Kohn-Sham density functional theory (KS-DFT) and Hartree-Fock (HF) methods to obtain reliable energy and electronic properties has been performed in this study using a simple test case. It is crucial to re-emphasize the key differences between these methods to address common conceptual difficulties that occur among freshmen studying basic computational chemistry. The results suggested that the eigenvalue theorem in determining ionization potential could be well implemented in the HF but not in the KS-DFT method. The total energy difference between ionized and non-ionized species was an appropriate procedure to calculate the first ionization potential within the KS-DFT method. The HOMO-LUMO gap in the HF was larger than the gaps obtained from the KS-DFT method. Among all of the performed calculation methods, the B3LYP hybrid functional provided better total energy where the eigenvalues were located between the HF and the LDA/GGA functionals.